Enhanced cellulose enzymatic hydrolysis of pilot-scale steam-exploded Eucalyptus grandis chips with previous acid impregnation for bioethanol production - Camila Bacquerié; Mairan Guigou; Florencia Cebreiros; Valeria Larnaudie; María E. Roman; Matías Cagno; Facundo Rodríguez; Fernando Bonfiglio; Mario D. Ferrari; Claudia Lareo (Energy Conversion and Management: X)
The enzymatic hydrolysis of cellulose from Eucalyptus grandis, pretreated through diluted acid impregnation and steam explosion in a continuous pilot-scale reactor, was evaluated for bioethanol production. The best pretreatment conditions were achieved at 180 °C and 0.5 % sulfuric acid, resulting in an enzymatic hydrolysis efficiency of 61.4 %. The liquid fraction contained up to 89 g/L of xylosaccharides, with a xylan recovery (expressed as xylose) of 50.6 %. The effects of solid content (16–24 % w/w), enzyme dose (15–25 FPU/gglucan), and pH (4.8–6) on enzymatic hydrolysis were assessed using a modified Box-Behnken experimental design. All factors, as well as the interaction between solid content and pH, were significant for achieving high glucose concentrations with high enzymatic hydrolysis efficiency. Higher pH values consistently enhanced hydrolysis efficiency. Multi-objective optimization identified the optimal conditions as pH 6, 24 % solid content, and an enzyme dose of 25 FPU/gglucan, maximizing glucose concentration (122 g/L), enzymatic hydrolysis efficiency (68 %), and glucose yield (49 %). Separate enzymatic hydrolysis and fermentation produced 52 g/L of ethanol, with an overall glucan-to-ethanol conversion efficiency of 46 %. In contrast, when pre-saccharification for 24 h was followed by simultaneous saccharification and fermentation, the performance was lower. Only minimal additional hydrolysis occurred during fermentation. These results contribute to the development of more efficient biomass-to-bioethanol conversion processes, supporting the development of sustainable energy technologies based on lignocellulosic resources.